Complex manipulation of microparticles exploiting the enhanced diattenuation of light in conjugation with phase contrast microscopy - Snigdhadev Chakraborty; Sauvik Roy; Srestha Roy; Jayesh Goswami; Gokul Nalupurackal; Krishna Kumari Swain; Ayan Banerjee; Basudev Roy (Journal of Physics Communications)
Manipulating subdiffractive particles with the polarization properties of a tightly focused laser has been very important in varied areas of research. In this paper, we determine that the intensity pattern formed before and after the focus of the Gaussian beam in stratified media differs significantly, and accordingly, the orientation and dynamics of surface-assisted optically trapped particles vary considerably depending on their trapping location. On another note, the most commonly used tool to visualize subdiffractive particles is Differential Interference Contrast (DIC) microscopy which can be used in conjugation with optical tweezers. However, this strongly affects the polarization of light on the sample plane, posing limits on particle manipulation using controlled polarization states of light. Here we use an external phase contrast microscopy system, where the phase ring is away from the objective, thus enabling micromanipulation with high resolution phase contrast microscopic visualisations. Towards micromanipulation, we generate a ring shaped optical trapping region close to the top surface of the sample chamber by focusing the laser a few μ m inside the top glass slide where particles can not only be trapped on the ring, but also moved in a circular trajectory by exploiting the effects of the enhanced diattenuation of light due to tight focusing - where the intensity profile may be modified by tuning the polarization of the linearly polarized input light. The motion on circular orbit works particularly well for high refractive index particles, and can usher a new domain of simultaneous complex manipulation and high quality visualization of nanoparticles, hitherto inaccessible in optical tweezers. We also show a typical application of such traps by performing magnetic field sensing.